Prevalence of Hapatitis Prevalence of Hepatitis C Virus and Human Immunodeficiency Virus Co-infection in Dr. Mintohardjo Navy Hospital, Jakarta - Suyanto Sidik (The Indonesian Society for Digestive Endoscopy, 2008)
Background: Today HIV/AIDS has become a major global health problem due to high rate of morbidity and mortality. Epidemiological data showed that many HIV-infected patients were co infected by hepatitis C virus (HCV) since both of these viruses share similar routes of transmission, with the most frequent modes of acquiring the infections are by sexual, parenteral, and perinatal transmission. The objective was to describe the profiles of HCV and HIV co-infection patients in Mintohardjo hospital Jakarta. Methods: This was a cross-sectional study in HIV patients who were treated in Internal Medicine Department of Mintohardjo hospital Jakarta from January 2006 to July 2007. Patient’s record was retrieved from Medical Record Department and we sought event rate of hepatitis C co-infection. Results: There were 114 patients were diagnosed as HIV positive in a several clinical staging treated during period of 1st January 2006 to 31st July 2007, 80.7% were men and their median age was 27 years old. The peak age group was 26-30 years old. Intravenous drug users (IDUs) were found in 73.7% of cases. Anti-HCV total antibody was found in 31.6% cases, including 1 non-IDUs. Sex was significantly correlated with the risk factor of HIV infection (r = 0.580, p 0.01), and educational background was also significantly correlated with the risk factor of HIV infection (r = 0.229, p 0.05). Conclusion: The prevalence of HCV and HIV co-infection in Dr. Mintohardjo Navy Hospital was 31.6%. There were a correlation between HCV infection and IDU, sex and risk factors, and also between educational background and risk factors. Keywords: HIV infection, hepatitis C infection, IDUs